An efficient artificial light-harvesting system with tunable emission in water constructed from a H-bonded AIE supramolecular polymer and Nile Red. Issue 80 (9th September 2020) - Xiao, Tangxin; Wu, Haoran; Sun, Guangping; Diao, Kai; Wei, Xiaoyan; Li, Zheng-Yi; Sun, Xiao-Qiang; Wang, Leyong
Abstract : An efficient artificial light-harvesting system with tunable emission in water was successfully constructed from a H-bonded AIE supramolecular polymer and Nile Red. Abstract : With the aid of CTAB amphiphile, water-phase artificial light-harvesting systems were fabricated as nanoparticles by the self-assembly of two low-molecular-weight organic molecules: a UPy-functionalized TPE derivative 1 with both supramolecular polymerization and AIE capabilities as a donor and a fluorescent chromophore NiR as an acceptor. Owing to the flexibility of supramolecular self-assembly, tunable emissions including white-light emission could be easily realized with high energy transfer efficiency and the antenna effect.